The Advertising Message and Approach Analysis of the Halal Toothpaste Product Category in Indonesia - Rasyid, Mohammad Ichsan (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to understand how the latest Advertising message and approach of the existing Halal Toothpaste Products in the Indonesian market. This study was conducted to provide Advertising Strategy recommendations. To Analyse the Advertising message and approach, this study used the Elaboration Likelihood Model as the analysis framework and utilize various Advertising approaches in executing Advertising Creative Strategy as references. This qualitative descriptive research tries to describe and compare the message and the approach of the latest Advertising campaign materials of Halal Toothpaste Products. Data were collected from the relevant documents, literatures and various online publications. The analysed Advertising campaign Materials were collected from YouTube. The Result shows that all the existing Halal Toothpaste products Advertising messages and approaches utilized the central route of mental process that elaborate the product ingredients and their benefit. The Halal attribute communicated verbally and visually, and was mainly driven by the product ingredients that were associated with Islamic culture in Indonesia. Practically, this study result will be a reference for Advertising practitioners on how to communicate Halal through Advertising. Academically, this study will be a reference for further thinking and research ideas on Halal Product Marketing Communication, Halal Product Advertising, and Halal Product Advertising Strategy.